Dark septate endophytic fungi and thiocyanate induced gold accumulation of Brassica juncea and Amaranthus spinosus grown on gold mine tailings - Septian, Renaldy Rachman; Sulistijorini; Surono; Hamim
Plants can absorb metals, including gold, making them potential as phytomining agents. This study investigated the ability of Brassica juncea and Amaranthus spinosus inoculated with Dark Septate Endophyte (DSE) fungi and treated with ammonium thiocyanate to accumulate gold (Au) from gold mine tailings. The plants were inoculated with DSE fungi (S14 and S51), referred to as D1 and D2, respectively, and a control group without inoculation (D0). They were grown in four media: Soil (T0), Tailing (T1), Tailing + ammonium thiocyanate 0.62 g/kg (T2), and Tailing + ammonium thiocyanate 1.24 g/kg (T3). Results indicated successful DSE colonisation across treatments, improving root and shoot dry weight, plant height, chlorophyll and carotene contents, and gold uptake. Thiocyanate enhanced gold absorption but caused plant death at high concentrations. A. spinosus transported more gold to shoots, while B. juncea accumulated more gold in roots. The highest phytomining potential was observed in B. juncea inoculated with DSE S14 (D1) in T2 media. These findings highlight the potential of combining plant species, DSE fungi, and chelating agents to optimise phytomining in gold-contaminated sites. DSE fungi not only enhanced gold uptake but also mitigated stress caused by tailings, offering an eco-friendly strategy for metal recovery. Future research should explore scalability and long-term impacts to strengthen phytomining as a sustainable alternative in gold mining reclamation efforts.